Surgical Management of Left Ventricular Outflow Tract Obstruction after Biventricular Repair of Double Outlet Right Ventricle - Kim, Chang Young (The Korean Academy of Medical Sciences, 2010)
Regardless of the preoperative morphology and the type of operation, left ventricular outflow tract obstruction (LVOTO) after biventricular repair of double outlet right ventricle (DORV) may develop. This report presents our 10-yr experience with surgical management of LVOTO after biventricular repair of DORV. Between 1996 and 2006, 15 patients underwent reoperation for subaortic stenosis after biventricular repair of DORV. The mean age at biventricular repair was 23.3±18.3 months (1.1-64.2). Biventricular repairs included tunnel constructions from the left ventricle to the aorta in 14 cases and an arterial switch operation in one. The mean left ventricle-to-aorta peak pressure gradient was 54.0±37.7 mmHg (15-140) after a mean follow-up of 9.5±6.3 yr. We performed extended septoplasty in nine patients and fibromuscular resection in six. There were no early or late mortality. There was one heart block and one aortic valve injury after an extended septoplasty, and two and one after a fibromuscular resection. No patient required reoperation for recurrent subaortic stenosis. The mean pressure gradient was 11.2±11.4 mmHg (0-34) after a mean follow-up of 5.6±2.7 yr. Extended septoplasty is a safe and effective method for the treatment of subaortic stenosis, especially in cases with a long-tunnel shaped LVOTO.